Effect of transplanting dates and mulching materials on growth, yield and economics of summer squash (Cucurbita pepo) in Uttarakhand hills - SINGH, MOHAN; BHATT, LALIT; SINGH, V P; MAURYA, S K; SINGH, AWANI KUMAR (The Indian Journal of Agricultural Sciences, 2015)
A study was undertaken to investigate the effect of different dates of transplanting and mulching materials on plant growth, yield and economics of summer squash (Cucurbita pepo L.) under rainfed condition in Uttarakhand hills during spring summer season of 2011 and 2012. Summer squash was mulched with black polyethylene, pine needle, FYM and dried leaves along with and without mulched (control) and transplanted at three different dates, i.e. 10 March, 25 March and 9 April in Factorial RBD replicated thrice. During the study, observations on plant height, plant spread, leaf area, days to 50 % flowering, number of harvesting, number of fruits/plant, total yield etc. were recorded. In addition, to assess the profitability of treatments cost of cultivation, net profit and benefit cost ratio were also worked out. Among three transplanting dates, 10 March was found to be best with respect to plant growth characters, total yield (61.35 tonnes/ha), net return (Rupees 452897/ha) and benefit cost ratio (3.82). Similarly, out of four mulches and control, black polyethylene mulch was observed the best with respect to plant growth characters, total yield (68.50 t/ha), net return (Rupees 449732/ha) and benefit cost ratio (3.58). So far interaction between transplanting dates and mulching materials used, out of 15 treatment combinations, D1M1 (transplanting on 10 March under black polyethylene) had recorded maximum yield of 76.03 tonnes/ha along with highest net profit of Rupees 582242/ha and benefit cost ratio of 4.27. Based on overall performance, it could be concluded that under the prevalent climatic condition of Uttarakhand hills, treatment combination D1M1 (transplanting on 10 March under black polyethylene) is the best and most economical treatment, hence, recommended for commercial cultivation at farmers fields, provided all other scientific management practices are followed.